Assessment of health-related quality of life and psychological well-being of children and adolescents with obesity enrolled in a New Zealand community-based intervention programme: an observational study. Issue 8 (9th August 2017) - Anderson, Yvonne C; Wynter, Lisa E; Treves, Katharine F; Grant, Cameron C; Stewart, Joanna M; Cave, Tami L; Wouldes, Trecia A; Derraik, José G B; Cutfield, Wayne S; Hofman, Paul L
Abstract : Objective: To describe health-related quality of life (HRQOL) and psychological well-being of children and adolescents at enrolment in a multidisciplinary community-based obesity programme and to determine association with ethnicity. This programme targeted indigenous people and those from most deprived households. Further, this cohort was compared with other populations/normative data. Methods: This study examines baseline demographic data of an unblinded randomised controlled clinical trial. Participants (recruited from January 2012-August 2014) resided in Taranaki, New Zealand, and for this study we only included those with a body mass index (BMI) ≥98th percentile (obese). HRQOL and psychological well-being were assessed using the Pediatric Quality of Life Inventory (PedsQL V.4.0 TM ) (parent and child reports), and Achenbach's Child Behavior Checklist (CBCL)/Youth Self Report (YSR). Results: Assessments were undertaken for 233 participants (45% Māori, 45% New Zealand European, 10% other ethnicities, 52% female, 30% from the most deprived household quintile), mean age 10.6 years. The mean BMI SD score (SDS) was 3.12 (range 2.01–5.34). Total PedsQL generic scaled score (parent) was lower (mean=63.4, SD 14.0) than an age-matched group of Australian children without obesity from the Health of Young Victorians study (mean=83.1, SD 12.5). In multivariable models, child and parental generic scaled scores decreased in older children (β=−0.70 and p=0.031, β=−0.64 and p=0.047, respectively). Behavioural difficulties (CBCL/YSR total score) were reported in 43.5% of participants, with the rate of emotional/behavioural difficulties six times higher than reported norms (p<0.001). Conclusions: In this cohort, children and adolescents with obesity had a low HRQOL, and a concerning level of psychological difficulties, irrespective of ethnicity. Obesity itself rather than ethnicity or deprivation appeared to contribute to lower HRQOL scores. This study highlights the importance of psychologist involvement in obesity intervention programmes. Trial registration number: Australian NZ Clinical Trials Registry ANZCTR 12611000862943; Pre-results.